Resilience-Thinking Training for College Students: Evidence from a Randomized Trial - Núria Rodríguez-Planas; Alan Secor; Rafael De Balanzó Joue (Institute of Labor Economics (IZA), 2023)
We conducted a randomized evaluation of a universal primary prevention intervention whose main goal was to increase the resilience of students from a large broad-access Hispanic Serving Institution and commuter urban college. In a 90-minute workshop, students were: introduced to the resilient-thinking approach, which offers conceptual tools to cope with unexpected negative shocks; worked individually and in groups to identify challenges in their community; and brainstormed strategies to address them. We find that the intervention increased by 5 percent of a standard deviation the short-run resilience of the average student. Importantly, the intention-to-treat effects were larger for students with lower levels of baseline resilience. The intervention was most effective among students with weaker individual protective factors at baseline (the most vulnerable students, those with lower resilience, and with higher mental health problems), and for those with stronger community protective factors, suggesting that individual and community factors mediate differently within this intervention. The intervention effects on students' resilience persisted over time. These effects were mostly driven by an improvement in students' collaboration (i.e., maintenance and formation of support networks and personal relationships), and vision (i.e., sense of purpose and belief in an ability to define, clarify, and achieve goals).
Keywords: I10; I18; I3; 330; resilience; randomized control trial; mental health; low-touch interventions; higher education; protective factors